PENGUATAN EKOSISTEM UMKM MELALUI KOLABORASI PEMERINTAH DAN DUNIA USAHA: MODEL KEMITRAAN DAN MANAJEMEN HUBUNGAN STAKEHOLDER - Uning Heri Gagarin; Jumadiah Wardati; Lidia Simanjuntak (Yayasan Nusantara Hasana Berdikari, 2024)
This Community Service (PkM) activity aims to strengthen the SME ecosystem through collaboration between the government and the business sector by developing an operational partnership model and a measurable stakeholder relationship management system. Common challenges include fragmented SME support programs, limited market access and financing, inconsistent quality standards, and cross-sector coordination that lacks established working mechanisms and shared indicators. The PkM intervention is carried out through mapping of stakeholders and SME needs, designing partnership models (governance, roles, service workflows), developing joint program packages (market access, product upgrading, financing, digitalization), and establishing a coordination platform in the form of a partnership forum and a KPI dashboard. Key outputs include partnership model documents, MoU/MOU templates, collaboration SOPs, stakeholder maps, and a 12-month action plan ready for implementation.